COVID-19 vaccines and therapeutics : insights on related patenting activity throughout the pandemic. (World Intellectual Property Organization, 2023)
Since the start of the COVID-19 pandemic there have been remarkable research and innovation efforts to fight the SARS-CoV-2 virus and the COVID-19 disease. This report provides observations based on a comprehensive review of the patenting activity that took place in the field of COVID-19 vaccines and therapeutics and builds on the insights discussed in the first WIPO COVID-19 Patent Landscape Report published in March 2022.
Keywords: Medicine -- Patents.; Medicine -- Research.; COVID-19 (Disease) -- Treatment.; Médecine -- Brevets d'invention.; Médecine -- Recherche.; COVID-19 -- Traitement.; Medicine.; Electronic books.; Patents.